I love Korean 4 - 사랑해요 한국어 4 Work Book (서울대학교출판문화원 Viện văn hóa xuất bảnTrường ĐH Seoul, 2019)
〈I Love Korean 4 Workbook〉 is a supplemental textbook for practice and review of the contents learned in the 〈I Love Korean 4〉 which was developed by the Seoul National University Language Education Center.